Resources for Sale: Corruption, Democracy and the Natural Resource Curse - Bulte, Erwin; Damania, Richard (2012)
A puzzling piece of empirical evidence suggests that resource-abundant countries tend to grow slower than their resource-poor counterparts. We attempt to explain this phenomenon by developing a lobbying game in which rent seeking firms interact with corrupt governments. The presence or absence of political competition, as well as the potential costs of political transitions, turn out to be key elements in generating the 'resource curse.' These variables define the degree of freedom that incumbent governments have in pursuing development policies that maximize surplus in the lobbying game, but put the economy off its optimal path.